Indigenous Employment Policy and Foreign-Owned Corporation Employee’s Well-Being in Liberia - Bankole, Taofik Olatunji; Gray, Daniel Denny; Oyebode, Abiodun Oluwaseun; Lawal, Gbelimu Elizabeth (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2019)
Every country institutes policy to take a course of action in favour of its citizens’ welfare. The view of indigenization policy in alignment with employment and workers treatment in Liberia takes different dimension. Liberia problem of unemployment cannot be compared to its underemployment and bad working conditions. The Liberian Indigenous policy has not reaped its fruit with marginalization, exploitation dispossession and poverty in commonplace. This study addresses the ineffectiveness of the indigenous employment policy and the state of workers’ well-being in foreign corporations in Liberia. This study adopts cross sectional method, and employs primary data. Information from 400 employees working with foreign-owned corporation was extracted from survey conducted in 2018 by the authors on the state of welfare of foreign-owned corporations’ employees in Liberia. The key explanatory variables are healthcare, social insurance, safety measures, stable job assignment, stable work hour, promotion on the job, and job security. The binary logistic regression was applied using version 22 of SPSS to examine association between the response and explanatory variables. The outcomes of this study showed that indigenous environmental policy was significant with worker’s well-being (p<0.05). The study concluded that indigenous employment policy has significant influence on the foreign-owned corporation workers’ well-being in Liberia.